2013
DOI: 10.1177/0163443713483796
|View full text |Cite
|
Sign up to set email alerts
|

The ‘social tsunami’: Media coverage of child abuse in Malaysia’s English-language newspapers in 2010

Abstract: Since the early 1990s, Malaysian society has displayed a deepening concern over steady increases in reported cases of child abuse in the country. For many Malaysians, knowledge of this issue comes from the mainstream media. This research analyses media coverage of child abuse in two mainstream English-language daily newspapers throughout 2010. The analysis focuses on how this issue is presented and ‘framed’ in the media. Through the use of simple episodic framing and a distorted focus on extreme cases of child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 24 publications
4
28
0
1
Order By: Relevance
“…These results are similar to findings in Australia , South Africa (Corbella and Collings, 2007); Malaysia (Niner et al, 2013) and some of the research in the US (Kunkel et al 2006;Mejia et al, 2012). It is interesting to note that Hove et al (2013) found that recent One would expect broadsheet newspapers to frame articles with a thematic analysis much more often than tabloid papers.…”
Section: Beyond 'Evil': the Importance Of Reporting Possible Causes Asupporting
confidence: 83%
“…These results are similar to findings in Australia , South Africa (Corbella and Collings, 2007); Malaysia (Niner et al, 2013) and some of the research in the US (Kunkel et al 2006;Mejia et al, 2012). It is interesting to note that Hove et al (2013) found that recent One would expect broadsheet newspapers to frame articles with a thematic analysis much more often than tabloid papers.…”
Section: Beyond 'Evil': the Importance Of Reporting Possible Causes Asupporting
confidence: 83%
“…Data were entered into SPSS (18.0). Articles were then coded according to basic typology of abuse such as, childmurder, sexual abuse, abandonment, or neglect (for extended reporting see Niner, Ahmad, and Cuthbert 2013). Once this was completed, all items were excluded that did not conform to child abuse as defined by the WHO:…”
Section: Methodsmentioning
confidence: 99%
“…Ayre 2001, 889). During these spikes the quantity of media coverage increased and more thematic articles appeared (Niner, Ahmad, and Cuthbert 2013).…”
Section: Frames and Coveragementioning
confidence: 99%
“…Until we began our own research (Razali, ; Razali et al ., , , ), there were no reports of filicide research in Malaysia (nor in neighbouring countries), and there was no way of knowing whether the phenomenon in Malaysia differed from what had been found elsewhere. In recent decades, filicide and infant abandonment have attracted media interest and increased public concern worldwide (Little and Tyson, ; Niblock, ), including in Malaysia (Niner et al ., ), where there are frequent accounts in the media of infants being abandoned or their bodies being found. This is discussed by opinion leaders as attributable to bad parenting, poor religious education, internet pornography and overexposure to sexual liberalism (Razali, ).…”
Section: Introductionmentioning
confidence: 99%